1947
DOI: 10.1172/jci101784
|View full text |Cite
|
Sign up to set email alerts
|

The Anemia of Infection. V. Fate of Injected Radioactive Iron in the Presence of Inflammation 1

Abstract: Since hypoferremia is so consistently associated with the anemia of infection (1), and since injected iron appears to be diverted from the plasma in infection (1, 2), it seemed desirable to determine the fate of the diverted iron.In this study, radioactive iron was injected intravenously into normal rats and in rats with acute inflammation. The blood and tissues were then analyzed after a period of time for radioactivity. Preliminary studies were made in which only the blood and liver were analyzed in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

1949
1949
1987
1987

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 6 publications
1
12
2
Order By: Relevance
“…Previous studies of iron metabolism in patients with chronic inflammation, including patients with rheumatoid arthritis, have shown diminished red cell utilization (26)(27)(28), and increased tissue deposition of injected radioiron (29). These studies differed from the present one in that the injected radioiron was not bound to transferrin, and the amounts of carrier iron injected often exceeded the total iron-binding capacity of the plasma.…”
Section: A Iron Metabolismcontrasting
confidence: 77%
“…Previous studies of iron metabolism in patients with chronic inflammation, including patients with rheumatoid arthritis, have shown diminished red cell utilization (26)(27)(28), and increased tissue deposition of injected radioiron (29). These studies differed from the present one in that the injected radioiron was not bound to transferrin, and the amounts of carrier iron injected often exceeded the total iron-binding capacity of the plasma.…”
Section: A Iron Metabolismcontrasting
confidence: 77%
“…Depression of the per cent saturation occurs in iron deficiency and in infections. It seems reasonable to explain the former on the basis of depletion of body iron and the latter on an increased affinity of tissue storage depots for iron (15).…”
mentioning
confidence: 99%
“…Indeed, experiments by Menkin (17,18) in the rabbit have indicated that iron accumulates in the inflamed area where, it is postulated, a beneficial function may be served. Our own studies in experimental animals (19), however, would suggest that the amount of iron so diverted is by no means adequate to account for the hypoferremia.…”
Section: Discussionmentioning
confidence: 68%